The genus Danielithosia Dubatolov & Kishida, 2012 (Lepidoptera, Erebidae, Arctiinae) in Cambodia, with description of one new species - Bayarsaikhan, Ulziijargal; Dubatolov, Vladimir V.; Bae, Yang-Seop (Zootaxa, 2015)
Although the arctiine fauna of Cambodia remains poorly known, considerable progress has been made over the last seven years (Bucsek, 2012; Cerny & Pinratana, 2009; Bae et al., 2012; Dubatolov, 2012, 2013; Dubatolov et al., 2012, 2013). The genus Danielithosia (Arctiinae) was established by Dubatolov and Kishida (2012), with the type species Tigrioides aureolata Daniel, 1954 from Fujian, Sichuan, and Zhejiang, China. To date, this genus comprises 11 species in the world, most of which are distributed in the Palaearctic and Oriental Regions (Dubatolov, 2013). The genus Danielithosia can be recognized by the following characters: sacculus with a characteristic broadening subapically; juxta long, with a long sclerotized bifurcated process apically (Dubatolov et al., 2012). In Cambodia, only one species, D. hoenei Dubatolov, 2013, has been reported (Dubatolov, 2013), and we here describe one new species from Cambodia. Terminology in this paper follows Dubatolov et al. (2012), and the specimens used in this study are deposited in the collection of Incheon National University (INU), on indefinite loan from Cambodia.